Community perception and participation of urban farming towards sustainability urban environment - Norul Hafizah binti Yusoff (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
This research sought to identify the importance of community perception and their participation in the urban farming activities to be implemented within cities environment. In addition, this research proved that conducting urban farming is beneficial to achieve sustainable urban environment for the enhancement of community function and healthy lifestyles that contribute in greening the urban landscape. This research describes the role of the community to achieve the environmental, economic and social sustainability through community awareness, engagement and supports in food supplies, nutrition and spaces utilization. Thus, the objective of this research is to investigate the community perceptions about the urban farming and its advantages, to evaluate the community participation and involvement in the urban farming activities as well as to determine the potential factor influences and challenges of urban farming activities to overcome the obstacles in the urban settings. Evaluation on the understanding, benefits and potential of urban farming activities within limited urban spaces and how it improves the quality of life are discussed. It is necessary to apply and practice in our daily lives for the consumption of food security, human safety, and health. In conducting data collection, this research employed mix-methods of qualitative and quantitative research approach. In total, 200 respondents answered the questionnaire surveys and 15 interviews are interviewed among urban communities within Kuala Lumpur, Selangor and Putrajaya residential areas. The research finds that in terms of perceptions, the finding shows that the familiarity, purposes and significance of urban farming activities signifies the awareness and understanding level from the urban community. It is reflected from the limitation of knowledge that have a significant contribution from deliberating respondents' background. The purpose of initiating urban farming give valuable insight the need of urban farming. The study finds out that time and space limitation being the major influences into the farming implementation within urban residential areas in Malaysia. Although several respondents agreed that they currently have already implementing urban farming activities around their residential areas, it has been proved from the study that workers, pensioners and housewives actively utilized several practical areas for farming but not students due to commitment constraints as well as lack of interest and motivation. This reason is supported by the interviewee opinions that addressed the issues of time management in their daily lives. From the urban sustainability findings, the research indicates that beneficial practices to grow a valuable complementary farming system which is yet to be recognized in Malaysia as the support from each community are required to make excellent promotion for everyone to realize and concern on the importance of growing foods in fast growing urban cities especially in terms of environmental, social, economic and healthy lifestyles. Therefore, the role of community is very crucial in the implementation of urban farming activities within urbanization areas due to the demands for green development is increases. Based on this theoretical framework, it hopes that this research will become useful knowledge in promoting a stronger community interdependence to create the sustainable urban environment.